(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: إنّ انتقال الجملة من البنية العميقة إلى البنية السطحية، لا يتحقق إلا عن طريق التحويلات المختلفة التي يمكن أن تحدث في الجملة الواحدة، وقد يكون الاختلاف بين البنية العميقة والبنية السطحية في الجانب التركيبي. وقد لا تتوافق في المسارين البنائي والدلالي، وهذا ناتج عن دخول عناصر التحويل المختلفة عليها. يهدف البحث الحالي المعنون بـ: تلقي البنى التحويلية وتأويلها في شعر النقائض، .... إلى الكشف عن عملية التحويل سواء كانت البنية العميقة متعددة والبنية السطحية ثابتة أو العكس، وذلك في شعر النقائض الذي له نسق خاص يميزه عن بقية الأغراض ...واتبع الباحثان المنهج الوصفي التحليلي كونه يتماشى وأهداف البحث. دلّت نتائج البحث أنّ هدف الجملة التحويلية هو إيصال فكرة محدّدة إلى متلق ما ... بشتى الطرق والوسائل وأحيانا تفاجئ المتلقي بخروجها عن النسق المعتاد .... على الرغم من أنها تحافظ على قوانين اللغة .... ويتوقف فهم القصد على مدى قدرة المفسّر في استنباط المعنى الذهني العميق أو السطحي للرسالة. كلمات دالة: بنية سطحية، بنية عميقة، تحويل، حذف، انتقال. Abstract: The transition of the sentence from the deep structure to the superficial structure is not achieved except through the different transformations that can occur in the same sentence, and the difference between the deep structure and the surface structure may be in the structural aspect. It may not coincide in the structural and semantic paths, and this is the result About the entry of the various elements of transformation into them. The current research, entitled: Receiving transformational structures and their interpretation in the poetry of contradictions , aims to reveal the transformation process, whether the deep structure is multiple and the surface structure is fixed or vice versa, in Poetry of contradictions, which has a special pattern that distinguishes it from the rest of the purposes ... The researchers followed the descriptive analytical approach, as it achieves the objectives of the research. The results of the research indicated that the goal of the transformative sentence is to convey a specific idea to a recipient...by various means and methods, and sometimes it surprises the recipient by deviating from the usual pattern....although it preserves the laws of language.... and the understanding of the intent depends on the ability of the interpreter In eliciting the deep or superficial mental meaning of the message. Key words: surface structure, Deep Structure, ransformation, delete, move.